ANALISIS LEVEL KOGNITIF LOTS DAN HOTS SISWA DALAM PEMBELAJARAN IPAS MENGGUNAKAN MODEL PEMBELAJARAN RADEC BERBANTUAN MEDIA FLIPBOOK DIGITAL - Ratna Ningrat, Ayu; Aldia Sundara, Fazar; Novitasari, Gita; Setiawati, Ina (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to describe the achievement of Lower Order Thinking Skills (LOTS) at the C2 and C3 levels and Higher Order Thinking Skills (HOTS) at the C4 level among sixth-grade students (Class 6A) of SDN 1 Awirarangan in IPAS (Natural and Social Sciences) learning Chapter 7 Topic A, implementing the RADEC (Read, Answer, Discuss, Explain, Create) model assisted by digital flipbook media. This research employed a quantitative descriptive approach. The subjects were 22 students consisting of 9 male and 13 female students, selected through purposive sampling. Data were collected using a multiple-choice evaluation test comprising 5 items covering cognitive levels C2, C3, and C4. Data analysis utilized descriptive statistics including mean, percentage of achievement per cognitive level, and distribution of achievement categories. The results revealed that the classical average score reached 82.73 with a mastery rate of 86.36%. LOTS achievement (C2+C3) reached 86.37% in the Very Good category, while HOTS achievement (C4) reached 77.27% in the Good category. The cognitive level distribution showed a consistent declining pattern: C2 (88.64%) > C3 (81.82%) > C4 (77.27%). Gender-based analysis indicated that male students achieved higher LOTS (92.59%) compared to female students (82.05%), whereas HOTS achievement was relatively equal between both groups (male 77.78%; female 76.92%). These findings indicate that the implementation of the RADEC model assisted by digital flipbook media contributes positively to students' cognitive level mastery, particularly in developing analytical thinking skills equitably across gender groups.